A speech act analysis of the prime minister's speech pertaining to the movement control order (MCO) to address the covid-19 pandemic in Malaysia / Maisarah Ahmad Kamil and Fatin Fatinah Shamshul Bahrn - Ahmad Kamil, Maisarah; Shamshul Bahrn, Fatin Fatinah (Universiti Teknologi MARA Shah Alam, 2020)
Crisis management is a competency that needs to be possessed by all leaders of today to address the challenges and volatility of the world today. The COVID-19 pandemic is one of the most crucial examples of such volatility which has impacted the world today. Malaysia is one of the countries that was initially badly affected by the pandemic, and matters were made worse with the political turmoil in the country when there was a change in the prime minister as the COVID-19 cases rose in the country. This study analyses the direct and indirect speech acts in the text of the Malaysian prime minister's speech on the first day the Movement Control Order (MCO) was implemented country-wide to curb the spread of the COVID-19 virus using the speech act theory by Searle (1969). From the direct speech act, the five classes of the illocutionary act (declaratives, representatives, expressive, directives, and commissures) were further identified and examined. The study found that expressive and directives were used the most in the direct speech acts, while the indirect speech acts carried the purpose to direct or persuade the audience. This study carries significance to the field of speech analysis and crisis management, as it depicts a strategy in which a country leader addresses its citizens during a time of political and worldwide crisis.